Genes, Gastronomy and Gratitude : The development and future of the conservation of native breeds - Ovaska, Ulla (University of Tampere, 2017)
The number of native breeds has diminished globally during the last decades. Many breeds have already become endangered or even extinct. The loss of native breeds is still continuing, which will ultimately lead to a global loss of their genetic resources (AnGR) and thereby a loss of agrobiodiversity. The modernisation of agriculture with new technologies and breeds has especially contributed to the situation in which native farm animals have been replaced by better-yielding breeds. Yet, there are multiple reasons to conserve breeds. Many are adapted to difficult climate conditions, and therefore play an important part in answering to future environmental challenges, such as climate change. In addition to their role in sustainable agriculture, there are other reasons to conserve native breeds including, e.g., their role in the landscape, cultural history and rural livelihoods. This research examines the development and future of the conservation of native breeds in two case studies: the conservation of the Yakutian Cattle in the Sakha Republic in the Russian Federation and the conservation of native breeds in Finland. The main research questions examine: how the need for conservation and its meanings have changed over time and what landmarks can be identified; how different actors have argued for the need for conservation, how discourses have developed and what kinds of coalitions have been formed; and how different arguments are translated into policies and policy-making and how the conservation is organised. The research setting comprises: 1) environmental governance dealing with institutions, actors and contents involved with agro-environmental policies, 2) ecosystem services about the benefits ecosystems produce for the well-being of humans and the values underlying these services, and 3) an institutional approach which contributes to understanding the realisation of policies in practice. These approaches provide three complementary perspectives on understanding the conservation of native breeds, its development and its future. The study revealed that despite different contexts in the conservation of native breeds, common milestones, arguments for conservation and challenges to it can all be identified. The conservation in both case studies has followed and contributed to international development, and has benefitted from the opportunities that have opened up to conservation at national and local levels. The arguments for the conservation of native breeds consist mainly of biological, economic, cultural and other social factors. Native breeds can be maintained if there are actors willing to aim for common goals. This requires cooperation between actors and institutions at different levels and sectors of conservation. The ES approach provides a feasible communication tool to achieve this. Alkuperäisrotuisten kotieläinten määrä on vähentynyt maailmanlaajuisesti viime vuosikymmenten aikana. Osa roduista on vaarassa hävitä tai jo hävinnyt kokonaan. Tämä johtaa niiden geenivarojen menetykseen ja samalla maatalouden biodiversiteetin vähenemiseen. Erityisesti maatalouden modernisaatio uusine teknologioineen ja rotuineen on johtanut siihen, että alkuperäisrotuja korvataan parempituotoksisilla eläimillä. Alkuperäisrotuja tulisi kuitenkin säilyttää lukuisista syistä. Ne ovat sopeutuneet vaikeisiin ilmasto-olosuhteisiin ja ovat siten tärkeitä varautumisessa tulevaisuuden ympäristöhaasteisiin kuten ilmastonmuutokseen. Alkuperäisrodut ovat tärkeä osa kestävää maataloutta ja niitä suojellaan mm. maisemallisten ja kulttuurihistoriallisten syiden vuoksi. Roduille on myös käyttöä maaseutuelinkeinoissa. Tässä opinnäytetyössä tutkitaan alkuperäisrotujen suojelun kehitystä ja tulevaisuutta kahden tapaustutkimuksen avulla. Ne ovat jakutiankarjan suojelu Sahan tasavallassa Venäjällä ja alkuperäisrotujen suojelu Suomessa. Tärkeimmät tutkimuskysymykset ovat: 1) kuinka suojelun tarve ja merkitys on muuttunut ajan myötä ja mitä virstanpylväitä voidaan tunnistaa; 2) kuinka eri toimijat ovat argumentoineet suojelun tarpeen puolesta, miten diskurssit ovat kehittyneet ja millaisia koalitioita on muodostettu ja 3) kuinka erilaiset argumentit ovat muotoutuneet suojelun politiikoiksi ja kuinka suojelu on järjestetty. Tutkimuksessa käytetään ympäristöhallinnan, ekosysteemipalveluiden ja institutionaalisen lähestymistavan käsitteitä. Ympäristöhallinta tarkastelee maatalouden ympäristöpolitiikkaan liittyviä instituutioita, toimijoita ja sisältöjä. Ekosysteemipalveluissa on kyse ekosysteemien ihmisten hyvinvoinnille tuottamista hyödyistä ja niihin liitetyistä arvoista. Institutionaalinen lähestymistapa analysoi politiikkojen käytännön toimeenpanoa. Lähestymistavat tuottavat kolme toisiaan täydentävää näkökulmaa alkuperäisrotujen suojelun, suojelun kehityksen ja tulevaisuuden ymmärtämiseen. Tutkimus osoittaa, että huolimatta suojelun erilaisista konteksteista, yhteisiä virstanpylväitä, argumentteja ja haasteita voidaan tunnistaa. Molemmissa tapaustutkimuksissa suojelu on seurannut kansainvälistä kehitystä ja myös myötävaikuttanut siihen. Suojelua on edistetty kansallisella ja paikallisella tasolla hyödyntämällä mahdollisuuksia, jotka suojelulle ovat avautuneet kansainvälisen kehityksen myötä. Alkuperäisrotujen suojelun puolesta argumentoidaan ennen kaikkea biologisin, taloudellisin, kulttuurisin ja muin yhteiskunnallisin syin. Alkuperäisrotujen säilyminen edellyttää yhteisiä tavoitteita sekä toimijoiden ja instituutioiden välistä yhteistyötä eri tasoilla ja sektoreilla. Ekosysteemipalveluiden käsite soveltuu kommunikaation apuvälineeksi.
Acta Electronica Universitatis Tamperensis nr. 1816
Keywords: ympäristönhallinta; maatalouden ympäristöpolitiikka; environmental governance; agro-environmental policy; geenivarat; biodiversiteetti; ekosysteemipalvelut; ympäristöpolitiikka; genetic resources; biodiversity; ecosystem services